Viscum album (mistletoe) extract for dogs with cancer? - Klingemann, Hans (Frontiers in Veterinary Science, 2024)
Compared with the options available to human patients with cancer, treatment choices for dogs are often more limited. Chemotherapy is frequently the first-line treatment for many cancers. However, its efficacy can be limited, and its side effects can affect the quality of the remaining life. This paper briefly summarizes the experience with Viscum album L. (mistletoe) extract in human patients as a stipulation to consider treatment with mistletoe extract for canines with cancer. The mistletoe extract contains -among others -lectins and viscotoxins that have documented anti-proliferative effect on cancer cells as well as immune-stimulatory function. Importantly, it also improves the well-being of patients with cancer due to its lectin ML-1 content, which can trigger the release of endorphins. Being cross-reactive with canine cells and having a relatively low side effect profile, it raises the question of whether mistletoe preparations might be considered as part of the treatment approach for 8 dogs with cancer.